Nomor Induk Berusaha (NIB) Jembatan Menuju Kesuksesan Bisnis yang Legal dan Terdaftar - Sari, Salsa Mulyana; Ramadanti, Aisyah Dwi; Putri, Silvi Rofiah; Maesaroh, Siti; Suryani, Suryani; Marfu'ah, Siti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The Business Identification Number (NIB) is a legal identity for businesses in Indonesia, issued through the online Single Submission (OSS) application. This article discusses the role of the NIB as a bridge to legal and registered business success, focusing on the implementation of OSS in the Warsun Dapur Puput area, Jl. Cilegon KM. 6, Keramatwatu. Using a qualitative descriptive approach, this article explores the benefits of the NIB in facilitating access to government services, such as business licensing, legal protection, and financing and marketing facilities. Furthermore, this article examines the technical and non-technical challenges faced by small and medium enterprises (MSMEs) in utilizing the OSS application, such as limited technological understanding and lack of mentoring. A case study in Warsun Dapur Puput shows that the presence of the OSS expedited the NIB registration process, enabling business actors to immediately operate their businesses with clear legal standing. This article recommends strengthening education and outreach on the OSS for MSMEs through collaboration between the local government and local communities. By optimizing the OSS, the NIB can become a strategic instrument for creating a legal, inclusive, and competitive business ecosystem at the local and national levels.